A Review on Biological Activity of Heterocyclic Nucleus Carbazole - Meghani, Monika; Mahawar, Pawan Kumar; Sharma, Kapil; Singh, Gurvindar (Asian Journal of Pharmaceutical Research and Development, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder associated with cognitive deterioration affecting day to day living and behavioural activities. It is commonest cause of senile and pre-senile dementia. In Alzheimer’s disease, a peptide referred as amyloid beta aggregates (oligomers), and accumulates in the brain to form deposits called as amyloid plaques. According to the world health organization (WHO), 5% of men and 6% of women of above 60 years are victims with Alzheimer’s type dementia globally. In India prevalence of dementia is 33.6%, of which AD contributes approximately 54% and vascular dementia constitutes approximately 39%. Patients with the prolonged use of some Non-steroidal anti-inflammatory (NSAID) drugs such as ibuprofen have lower risk of developing the symptoms of AD; however the chronic use of NSAID can produce a toxic effect on the kidney, liver and GI tract. Recent studies have demonstrated that a curcumin delivery system based on nanoscience and nanotechnology increases the therapeutic potential of this compound. Specifically, several nano-sized carriers such as phospholipid vesicles (liposomes), micelles, solid lipid nanoparticles, polymeric nanoparticles, emulsions, proteins and other molecular complexes have been developed for the efficient delivery of curcumin. Nano particles have demonstrated the enhanced Bioavailability of curcumin including circulation time in the blood. Various nano technology drug delivery system of curcumin showed increased Bio accessibility during treatment of Alzheimer’s disease.